EFL Algerian Doctoral Candidates’ Perceptions and Attitudes Towards Research Articles Writing - Benzahia , Toufik; Hamada, Hacène (Journal of Human Sciences, 2023)
Academic community members share the findings of their research projects through research articles publication. Likewise, the Algerian doctorate students find it mandatory to publish their research findings that are most pertinent to the topic of their doctorate thesis. However, most candidates find this task challenging because of inadequate understanding of academic genre norms and writing skills. This study explores EFL Algerian doctoral candidates’ perceptions and attitudes of writing research articles in order to determine the most common encountered difficulties, and suggests adequate strategies to solve their academic writing problems. Data collection was carried out through the use of a questionnaire administered to a sample of doctoral candidates and an interview of two academic writing teachers at Biskra University. The qualitative and quantitative data analysis determined that doctorate candidates face some academic writing problems because of inappropriate and scarce practice opportunities of this academic genre.